Isolation and Identification of Mycobacterium from Extrapulmonary Specimen at NTRL, NIDCH - Kamal, SM Mostofa; Ahasan, HAM Nazmul; Ahmed, Sharmin; Ayaz, KFM; Mahbub, Md Shahriar; Khan, Mohammad Ashik Imran; Gupta, Ratan Das; Alam, Md Billal; Miah, Md Titu (Journal of Medicine, 2010)
Objective of the study was to see the frequency of isolation of Mycobacterium among different extrapulmonary specimens. The study was carried out at NTRL (National Tuberculosis reference laboratory), NIDCH Bangladesh during January 2008-June 2009.This study was carried out retrospectively by analyzing NTRL laboratory data. A total of 514 extra-pulmonary specimens from different treatment centre of Dhaka was analyzed. Clinical specimens, such as lymph node aspirate, pleural fluid, urine, stool, gastric lavage, pus, ascitic fluid, cerebrospinal fluids, etc was collected. Lowenstein-Jensen media was used for culture and antimicrobial susceptibility testing. Mycobacteria were isolated from 113 extra-pulmonary specimens. Male and female ratio was almost equal among positive cases. The commonest source of isolation was lymph nodes(frequency 55.8%) and lymph node aspirate( frequency 68.4%) pleural fluid (frequency10.6%).Anti-microbial susceptibility of the isolates to the four first line anti-tuberculosis drugs, rifampicin, isoniazid, streptomycin and ethambutol was tested, susceptibility rate was 100%.The results suggest that,, emphasis should be placed on laboratory diagnosis and treatment of extra-pulmonary tuberculosis. Keywords: Pulmonary tuberculosis; extrapulmonary; Microbial Sensitivity Test; Laboratory Technics and Procedures; Bangladesh DOI: 10.3329/jom.v11i2.5454 J MEDICINE 2010; 11 : 128-130